Surviving water scarcity: seasonal contrasts in drought and desiccation tolerance of co-occurring Barbacenia gentianoides and Vellozia caruncularis - Vieira, Evandro Alves; da Silva, Giselly Mota; Gaspar, Marilia; Braga, Marcia Regina; Caldeira, Cecilio Frois (Frontiers in Plant Science, 2025)
Campos rupestres are tropical highland ecosystems characterized by herbaceous vegetation, high biodiversity, and elevated levels of endemism. Recognized as global biodiversity hotspots, they are increasingly threatened by intense anthropogenic pressures. Plants inhabiting these ecosystems face harsh environmental conditions, including dry winters, intense solar radiation, and shallow, quartzite-derived soils with low water retention capacity. This study examines the differential drought responses of two co-occurring Velloziaceae species, Barbacenia gentianoides and Vellozia caruncularis, throughout the seasonal cycle under natural field conditions. Ecophysiological and metabolic analyses reveal that B. gentianoides copes with the dry season by reallocating carbon to the leaf base during senescence, supporting leaf resprouting at the onset of the rainy season. In contrast, V. caruncularis exhibits desiccation tolerance by preventing senescence in younger leaves during the dry season and maintaining their structural integrity upon rehydration. Distinct metabolic shifts in sugars, amino acids, and secondary metabolites underscore the contrasting strategies of the two species: V. caruncularis emphasizes osmoprotection and reactive oxygen species (ROS) scavenging, whereas B. gentianoides focuses on starch and polyol storage for the production of new leaves. Differences in hormone signaling and flavonoid accumulation further underscore species-specific responses, contributing to the regulation of extreme dehydration tolerance in V. caruncularis and facilitating ethylene-mediated senescence as a survival strategy in B. gentianoides. Given the limited understanding of drought and desiccation tolerance mechanisms in native rock outcrop species under natural conditions, our findings offer valuable insights into the metabolic adaptations that enable survival in these unique and challenging ecosystems.